Trabalho e imigração: trabalhadores haitianos em Cascavel-PR (2012-2020) - Carvalho, Joselene Ieda dos Santos Lopes de (2020)
In this research, I sought to analyze and discuss three fundamental points in the narratives of Haitian immigrants who live or have lived in Cascavel, a city located in the western region of Paraná: i) life trajectories; ii) immigration trajectories; iii) trajectories of work and struggle. The main source of this work was the interviews conducted between 2016 and 2020 based on the theory-methodology of oral history, having as theoretical referential authors such as: Alessandro Portelli and Alistair Thomson. Understanding immigration as a predominant choice in the lives of Haitians, it was necessary to analyze not only the moment they arrived in Brazil, but their previous experiences that gave meaning to the immigration context. In this way, it was possible to understand immigration as a historical process full of challenges and uncertainties. The city of Cascavel became the focus of immigration due to the industries installed in this place that invest in the “development” discourse, in particular the refrigerators of Coopavel and Globoaves. This first slaughterhouse, in 2013, together with other companies in the southern region of Brazil, was to screen for the choice of immigrants who were in the Acre campground in order to bring them to work on the production line. Thus, these were the two main forms of work highlighted in the narratives: the production line of the slaughterhouses and the civil construction. The main objective of Haitian workers who immigrated to Cascavel was the relentless search for work so that they could survive and send remittances of their wages to their families who remained in Haiti. However, daily challenges experienced by these workers were presented, such as: the difficulty of the language, unemployment, the terrible working conditions, the precarious housing, the lack of public policies, among other situations of stigmatization to which they were constantly subjected. Therefore, in 2016, the Haitian Association of Cascavel was created, an autonomous institution organized by Haitians, whose founders and members seek to find better living conditions for survival in this city. Therefore, I consider it essential to write the History of the situations experienced by these workers for the construction of studies related to the world of work.